(untitled) (American Scholar: Journal of Interdisciplinary Research and Knowledge, 2026)
Abu Rayhan al-Biruni is widely recognized as one of the most prominent scholars of the medieval scientific world and a major representative of the intellectual tradition of the Islamic Golden Age. His scientific works covered a wide range of disciplines, including astronomy, mathematics, geography, mineralogy, philosophy, and history. The purpose of this article is to analyze Biruni’s contribution to world science and examine the methodological principles that formed the basis of his research. The study applies historical and analytical approaches to evaluate his works and scientific ideas. The results show that Biruni made significant contributions to the development of empirical observation, comparative analysis, and interdisciplinary research. His emphasis on the verification of knowledge through observation and experimentation demonstrates an advanced scientific methodology that anticipated principles of modern science. The article concludes that Biruni’s intellectual heritage remains an important foundation for the development of scientific thinking and continues to influence contemporary research traditions.